Mathematical simulation on the surface temperature variation of fresh-cut leafy vegetable during vacuum cooling. (May 2016) - Song, Xiao-yan; Liu, Bao-lin; Jaganathan, Ganesh K.
Highlights: Surface temperature of fresh-cut leafy vegetable during vacuum cooling is simulated. Effects of vein, leafy part and petiole on heat transfer are integrated in the model. Temperature changing regularities of leafy part and petiole are different. Temperature change of every location is related to its structure. Abstract: A numerical simulation by using a commercial software named COMSOL MULTIPHYSICS @ V4.4 was carried out to predict the heat transfer process in fresh-cut leaves of Brassica chinensis during vacuum cooling. The temperature distribution and the average surface temperatures of the leafy part and the petiole were predicted and compared with the experimental data. Both the experimental and simulated results followed the same time–temperature curves. The evaluated results show that the R 2 values were 0.9837 and 0.9876 for the average surface temperatures of the leafy part and the petiole, respectively. Further, the maximum differences between the experimental and simulated average surface temperatures at any time did not exceed 0.91°C and 0.83°C for the leafy part and the petiole, respectively. This indicates that the simulation outcomes are in great agreement with the experimental results.